Construction of an octosyl acid backbone catalyzed by a radical S-adenosylmethionine enzyme and a phosphatase in the biosynthesis of high-carbon sugar nucleoside antibiotics. Issue 1 (5th September 2016) - He, Nisha; Wu, Pan; Lei, Yongxing; Xu, Baofu; Zhu, Xiaochen; Xu, Gudan; Gao, Yaojie; Qi, Jianzhao; Deng, Zixin; Tang, Gongli; Chen, Wenqing; Xiao, Youli
Abstract : This work provides, for the first time, significant in vitro evidence for the biosynthetic origins of octosyl acid through free radical and dephosphorylation enzymatic reactions. Abstract : Unique bicyclic octosyl uronic acid nucleosides include ezomycin, malayamycin, and octosyl acid (OA). They are structurally characterized by OA, an unusual 8-carbon furanosyl nucleoside core proposed to be the precursor to polyoxin and nikkomycin. Despite the well-known bioactivity of these nucleoside antibiotics, the biosynthesis of OA has not been elucidated yet. Here we report the two pivotal enzymatic steps in the polyoxin biosynthetic pathway leading to the identification of OA as a key intermediate. Our data suggest that this intermediate is formed via a free radical reaction catalyzed by the radical S -adenosylmethionine (SAM) enzyme, PolH, and using 3′-enolpyruvyl uridine 5′-monophosphate (3′-EUMP) as a substrate. Subsequent dephosphorylation catalyzed by phosphatase PolJ converts the resulting octosyl acid 5′-phosphate (OAP) to OA. These results provide, for the first time, significant in vitro evidence for the biosynthetic origins of the C8 backbone of OA.